You Can't Take It with You? Immigrant Assimilation and the Portability of Human Capital - Friedberg, Rachel M. (Journal of Labor Economics, 2000)
The national origin of an individual's human capital is a crucial determinant of its value. Education and labor market experience acquired abroad are significantly less valued than human capital obtained domestically. This difference can fully explain the earnings disadvantage of immigrants relative to comparable natives in Israel. Variation in the return to foreign schooling across origin countries may reflect differences in its quality and compatibility with the host labor market. The return to foreign experience is generally insignificant. Acquiring additional education following immigration appears to confer a compound benefit by raising the return to education acquired abroad. Copyright 2000 by University of Chicago Press.